2017
DOI: 10.7726/jame.2017.1001
|View full text |Cite
|
Sign up to set email alerts
|

MHD Laminar Flows and Heat Transfer Adjacent to Permeable Stretching Sheets with Partial Slip Condition

Abstract: The aim of the present paper is a theoretical analysis of a steady Magnetohydrodynamic laminar flow of an incompressible viscous and electrically conducting fluid adjacent to permeable stretching sheet with partial slip condition has been carried out considering the effects of the involving governing physical parameters such as suction/injection parameter, velocity exponent parameter, buoyancy or mixed convection parameter, temperature exponent parameter, Prandtl number, and magnetic field parameter are studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Kafousius and Rees [4] concluded that when viscosity of any working fluid is sensitive to temperature variation, the effect of temperature-dependent viscosity has to be considered otherwise considerable errors may results in the heat transfer characteristics. Other correlated studies can be seen in Iyer et al [5], Ingham and Pop [6], Neild and Bejan [7], Urbano and Nasuti [8], Daniel [9] and Prenay et al [10].…”
Section: Introductionmentioning
confidence: 96%
“…Kafousius and Rees [4] concluded that when viscosity of any working fluid is sensitive to temperature variation, the effect of temperature-dependent viscosity has to be considered otherwise considerable errors may results in the heat transfer characteristics. Other correlated studies can be seen in Iyer et al [5], Ingham and Pop [6], Neild and Bejan [7], Urbano and Nasuti [8], Daniel [9] and Prenay et al [10].…”
Section: Introductionmentioning
confidence: 96%
“…Further, Daniel and Daniel 40 considered the effects of buoyancy and thermal radiation on MHD flow over a stretching porous sheet using the homotopy analysis method. Moreover, Daniel [41][42][43][44][45] studied the MHD laminar flow and heat transfer of a nanofluid over a linear/nonlinear permeable surface with slip boundary conditions. Bég et al 46 examined the energy conservation of NFs from a biomagnetic needle in the presence of Stefan blowing.…”
Section: Introductionmentioning
confidence: 99%
“…Daniel et al (2018a) studied the laminar convective boundary-layer slip flow over a flat plate by the homotopy analysis method. Daniel (2017) studied thermal stratification effects on the MHD radiative flow of the nanofluid over a nonlinear stretching sheet with variable thickness. Daniel et al (2018b) studied MHD laminar flows and heat transfer adjacent to permeable stretching sheets with a partial slip condition.…”
Section: Introductionmentioning
confidence: 99%